IMPLEMENTASI STRATEGI INQUIRING MINDS WANT TO KNOW PADA PEMBELAJARAN IPA KELAS IV B DI MI MAARIF BEGO - Sartawi Sartawi (Abdau: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
One way to increase students' learning interest is by using learning strategies. An interesting strategy will certainly influence learning process in order to produce quality learning, especially in science learning. Of the various types of strategies, researcher employs the Inquiry Mind Want to Know strategy in class IV B science learning at MI, Maarif Bego Yogyakarta. The study aims to determine the implementation, both the advantages and disadvantages factors, of the Inquiry Mind Want to Know Strategy in class IV B science learning at MI Maarif Bego Yogyakarta.The study uses a descriptive qualitative approach using the case study method. The data are collected through observation, interviews, and documentation. The analysis techniques applied are data collection, data reduction, data presentation and conclusions. Finally, the data are validated using the triangulation technique.The results of the study show that there are several ways of implementing the Inquiry Mind Want to Know Strategy in science learning i.e. implementation based on the steps of the Inquiry Mind Want to Know strategy, combining the Mind Want to Know strategy with contextual teaching and learning (CTL), and using practicing learning. The disadvantage in the strategy is inadequate time for students. Whereas the advantages of the strategy are that the students can be active and have enjoyable learning. The impacts of the Inquiry Mind Want to Know strategy on science learning are the students become more active and full of curiosity in the learning process and they can develop their skills and attitudes. Furthermore, using the strategy, the teachers have more understanding on their students.